Gauge Boson Mixing in the 3-3-1 Models with Discrete Symmetries - P. V. Dong; V. T. N. Huyen; H. N. Long; H. V. Thuy (Advances in High Energy Physics)
The mixing among gauge bosons in the 3-3-1 models with the discrete symmetries is investigated. To get tribimaximal neutrino mixing, we have to introduce sextets containing neutral scalar components with lepton number L=1,2. Assignation of VEVs to these fields leads to the mixing of the new gauge bosons and those in the standard model. The mixing in the charged gauge bosons leads to the lepton number violating interactions of the W boson. The same situation happens in the neutral gauge boson sector.